PENGARUH MODEL BLENDED LEARNING TERHADAP KETERAMPILAN PROSES SAINS DAN HASIL BELAJAR SISWA DI SMA YPK PEMATANGSIANTAR - Perayanti Sinaga, Dian; Novita, Dini (Program Studi Pendidikan Biologi, Fakultas Keguruan Dan Ilmu Pendidikan Universitas Simalungun, 2021)
This study aims to determine the effect of the Blended Learning model on science process skills and student learning outcomes at SMA YPK Pematangsiantar in the 2020/2021 Academic Year. The population was 105 students consisting of 3 classes. The control class (X IPA-3) consisted of 35 students and the experimental class (X IPA-1) consisted of 35 students. The control class (X IPA-3) was treated using the lecture learning method and the experimental class (X IPA-1) was treated using the blended learning model. From the t-test results, the t-value was obtained > t table, namely 2.546 > 1.667 at a significance level of α = 0.05 and degrees of freedom (df) = 54, so H0 was rejected and Ha was accepted, meaning there was an effect of the blended learning model on the science process skills of grade X students on the ecosystem material at SMA YPK Pematangsiantar in the 2020/2021 Academic Year. The posttest results for the control class (X IPA-3) were 93.48 and for the experimental class (X IPA-3) 94.74. The t-test results showed a calculated t value > t table, which was 2.227 > 1.667 at a significance level of α = 0.05 and 69 degrees of freedom (df). Therefore, H0 was rejected and Ha was accepted. This means that the use of the blended learning model has an effect on the learning outcomes of 10th-grade students in the ecosystem topic at SMA YPK Pematangsiantar. It was concluded that the use of the blended learning model has an effect on the science process skills (SPS) and learning outcomes of 10thgrade students in the Ecosystem topic at SMA YPK Pematangsiantar in the 2020/2021 academic year.